Klinische Studien in der Chirurgie: auf dem Weg zur evidenzbasierten Chirurgie - Diener, Markus K.; Knebel, Phillip; Fink, Christian; Dörr-Harim, Colette; Rossion, Inga; Werner, Jens; Büchler, Markus W. (Der Chirurg, 2012)
The Study Centre of the German Surgical Society (SDGC) aims at a sustainable support of clinical trials in surgery. The SDGC focuses especially on the development and conducting of clinical trials in university and non-academic hospitals. This article outlines current fields of action and future perspectives of the SDGC.